Exploring Digital Literature Literacy and Reading Through a Gender Lens - Raffaella Leproni (Asparkía)
Digital Literature (DL) has emerged as a significant artistic expression, challenging traditional storytelling and engaging audiences in new ways. This paper explores Digital Literature, DL Literacy (DLL), and their intersection with gender perspectives. Attempting to provide a definition for DL, drawing from sources like the Electronic Literature Organization (ELO) and scholars’ insights, various forms of e-literature are examined, emphasizing technological skills, critical thinking, and interpretive abilities. Strategies for developing DLL, including engaging with diverse texts and online collaboration, are also discussed. Central to the paper is how gender influences digital literary creation, distribution, and reception, highlighting implications for societal norms and stereotypes, and advocating for inclusive approaches and ethical storytelling practices to spark digital literary engagement.